2021
DOI: 10.3390/pharmaceutics13091443
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Robust Control Strategy for Fixed-Dose Combination Bilayer Tablets with Integrated Quality by Design, Statistical, and Process Analytical Technology Approach

Abstract: Control strategy and quality by design (QbD) are widely used to develop pharmaceutical products and improve drug quality; however, studies on fixed-dose combination (FDC) bilayer tablets are limited. In this study, the bilayer tablet consisted of high-dose metformin HCl in a sustained-release layer and low-dose dapagliflozin l-proline in an immediate-release layer. The formulation and process of each layer were optimized using the QbD approach. A d-optimal mixture design and response surface design were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…2C. From the DSC and the FTIR studies, it can be concluded that Metformin HCl is highly compatible with other excipients used in the formulation 11,12 .…”
Section: Fig 3: Ftir Spectrum Of Metformin Hcl (2a) Its Mixture With ...mentioning
confidence: 94%
“…2C. From the DSC and the FTIR studies, it can be concluded that Metformin HCl is highly compatible with other excipients used in the formulation 11,12 .…”
Section: Fig 3: Ftir Spectrum Of Metformin Hcl (2a) Its Mixture With ...mentioning
confidence: 94%
“…This is demonstrated by the work of Chun et al, 2021 in which bilayer tablets were manufactured consisting of high-dose metformin in a sustained-release layer with low-dose dapagliflozin L-proline incorporated into an immediate-release layer. The optimized bilayer tablet showed similar in vitro and in vivo profiles to the reference drug, demonstrating bioequivalence of the test product and the control drug [ 171 ]. The same concept is demonstrated by Vimovo ® (Grünenthal; naproxen, esomeprazole 500/20 mg), which has been developed as a sequential-delivery tablet system comprising an outer immediate-release esomeprazole layer with an enteric coated naproxen core [ 172 ].…”
Section: Formulation Approachesmentioning
confidence: 99%
“…OFAT approach requires a large number of experiments and does not allow evaluation of the interaction that exists between the factors, which may lead to inadequate conduction of the development and optimization. To overcome these problems, design of experiment (DoE) strategies are recommended to obtain better results with few numbers of experiments [ 34 , 35 , 36 , 37 , 38 ]. For developing CBD ODTs, a two-level full factorial design with three variables was used.…”
Section: Introductionmentioning
confidence: 99%